2020
DOI: 10.1016/j.redox.2020.101725
|View full text |Cite
|
Sign up to set email alerts
|

Glutathionylated and Fe–S cluster containing hMIA40 (CHCHD4) regulates ROS and mitochondrial complex III and IV activities of the electron transport chain

Abstract: Human MIA40, an i nter m embrane s pace (IMS) import receptor of mitochondria harbors twin CX9C motifs for stability while its CPC motif is known to facilitate the import of IMS bound proteins. Site-directed mutagenesis complemented by MALDI on in vivo hMIA40 protein shows that a portion of MIA40 undergoes reversible S-glutathionylation at three cysteines in the twin CX9C motifs and the lone cysteine 4 residue. We find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Studies have shown that Complex I and Complex III containing super-complex hastens the delivery of electrons via CoQ and thereby increases electron transfer efficiency 26 . To further understand the lowered state III respiration displayed by LDM, we measured super complex I + III and II + III coupled activities described previously [27][28][29] . Super complex I + III and II + III activities were carried out using equal concentrations of LDM and CM as described in the methods section.…”
Section: Ldm Is Bioenergetically Differentiatedmentioning
confidence: 99%
“…Studies have shown that Complex I and Complex III containing super-complex hastens the delivery of electrons via CoQ and thereby increases electron transfer efficiency 26 . To further understand the lowered state III respiration displayed by LDM, we measured super complex I + III and II + III coupled activities described previously [27][28][29] . Super complex I + III and II + III activities were carried out using equal concentrations of LDM and CM as described in the methods section.…”
Section: Ldm Is Bioenergetically Differentiatedmentioning
confidence: 99%
“…On the one hand, the import of proteins to the mitochondrial matrix relies on a disulfide-exchange relay system; on the other hand, GRX1 has been identified to reside in IMS, pinpointing the observation that S-glutathionylation may play a crucial role in IMS [ 70 ]. However, a recent study showed that the human S-glutathionylation of MIA40, an IMS import receptor, facilitates the maintenance of ROS levels and the optimal function of CIII and CIV [ 71 ]. This mechanism highlights the interconnection between ROS levels, protein S-glutathionylation and mitochondrial respiration ( Figure 3 ).…”
Section: Protein S-glutathionylationmentioning
confidence: 99%
“…Through this post-translational modification, cysteine residues in IMS proteins could be modified by ROS and RNS, with implications for redox signalling. Recently, it has been proposed that human Mia40 (CHCHD4) undergoes glutathionylation, which is then capable of transferring electrons directly to cytochrome c [ 74 ]. These authors suggest that glutathionylation of human Mia40 occurs to control the levels of ROS levels normally produced by electron transfer complexes III and IV.…”
Section: Small Redox Molecules and Redox Homeostasis In The Imsmentioning
confidence: 99%